Edukasi Penggunaan Papan Alur Sebagai Media Bermain Edukatif Untuk Meningkatkan Kemampuan Motorik Halus Pada Siswa PAUD Islam Terpadu Royyan Kids - Arif Pristianto; Dadang Hawari; Hidayatun Nisa; Rozalina Anisyah; Wildan Ahmad; Riski Dwi (Insight Power (Kekuatan Wawasan), 2022)
Fine motor skills are a child's ability to move by using smooth (small) muscles. Fine motor activities are the first step for children's maturation before they go to school. Children need careful preparation from an early age so that later they are expected to be able to master the movements that will be carried out at school. Age under 5 years is a golden age for children, so that what is seen and heard will be easily captured or accepted by the child's brain. To prevent inappropriate child development, it is necessary to play media that can provide positive and beneficial things for children. One of the games that have benefits for early childhood is the groove board game. This game is given to find out and improve fine motor development in children. Flowboard media will increase children's enthusiasm and attention in learning because it uses the principle of learning while playing. The goal is learning on fine motor skills that are useful for helping to flex stiff muscles and increase strength for muscles. In addition, it can increase concentration in coordination of motion with sight (sensomotor). The result of this activity is that children feel happier and teachers can make this activity a variation in learning.Keywords: fine motor, groove board, educational games, children's games